Right heart function interacts with left ventricular remodeling after CRT: A pressure volume loop study. (1st October 2018) - Schmeisser, Alexander; Rauwolf, Thomas; Ghanem, Ali; Groscheck, Thomas; Adolf, Daniela; Grothues, Frank; Fischbach, Katharina; Kosiek, Ortrud; Huth, Christof; Kropf, Siegfried; Lange, Stefan; Luani, Blerim; et al.
Abstract: Background: Right ventricular (RV) dysfunction is recognized as a cardinal prognostic marker in systolic heart failure patients. Conflicting data exist on the interaction of RV function and left ventricular (LV) reverse remodeling after cardiac resynchronization therapy (CRT). This prospective monocentric trial was set up to assess the predictive value of baseline RV function and corresponding RV-pulmonary artery (PA) coupling on LV reverse remodeling after CRT. Methods: 110 patients with a CRT indication were prospectively enrolled. RV function and RV-PA interaction were analyzed at baseline using echocardiographic and invasive pressure-volume loop catheter approach. The primary endpoint was reverse LV remodeling (CRT-responder) defined as a reduction in LV end-systolic volume of ≥15% at 6 months. Results: Responders had higher RV-PA coupling ratios (single-beat end-systolic elastance/PA elastance: Ees/Ea) at baseline, which corresponded to smaller RVs with better ejection fraction and lower afterload. After multivariate adjustment, the baseline Ees/Ea remained an independent predictor for LV response (OR 14.0 [1.5–130.8], p = 0.021). Normal coupling (Ees/Ea ≥ 1) was associated with higher responder rates (RR) (86%). Progressive uncoupling was associated with lower LV-RR (Ees/Ea ≤ 1–0.5: 57%, and Ees/Ea < 0.5: 32%, p < 0.001), corresponded with higher degrees of LV impairment and severity of mitral regurgitation, and was independently associated with an adverse outcome. Conclusions: A higher baseline RV-PA coupling, reflecting a lower degree of LV-induced pulmonary hypertension and secondary RV-dysfunction, is associated with an improved LV-reverse remodeling and is independently associated with better prognosis. The value of RV-PA ratio as potential guide for CRT patient selection warrants further investigation. Clinical Trial Registration – URL:http://www.drks.de . Unique Identifier: DRKS00011133. Highlights: Impact of RV coupling on LV remodeling after CRT implantation RV-PA coupling reflects the degree of LV dysfunction and mitral regurgitation. RV-PA coupling is an independent predictor of prognosis in CRT-D therapy.